Effect of particle size reduction on the physicochemical and mechanical properties of conventional glass ionomer cement - Tuygunov, Nozimjon; Abdurahimova, Farangis; Rizaeva, Sevara; Khurshid, Zohaib; Cahyanto, Arief; Zakaria, Myrna Nurlatifah; Khudanov, Bakhtinur (Frontiers in Dental Medicine, 2025)
BackgroundConventional Glass Ionomer Cement (GIC) is widely used in restorative dentistry due to its biocompatibility and fluoride release; however, its limited mechanical strength and bioactivity restrict its broader clinical applications. Reducing glass powder particle size represents a promising approach to enhancing its physicochemical performance.ObjectiveTo investigate the effect of glass powder particle size reduction on the physicochemical and mechanical properties of a conventional GIC.MethodsFour groups of conventional GIC were prepared by modifying glass powder particle size through one- or two-step ball milling. Particle size distribution (PSD) and field emission scanning electron microscopy (FE-SEM) were used to verify particle morphology, while energy dispersive x-ray spectroscopy (EDX), x-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR) confirmed chemical composition. The groups included: A – submicron (average 576.9 nm), B – nano (average 92.4 nm), C – hybrid (average 352.6 nm; composed of both nano and submicron particles), and D – control (936.8 nm, unmodified). Evaluations included pH, fluoride, and calcium ion release (over 28 days), initial setting time, compressive strength, and diametral tensile strength. Data were analyzed using one-way analysis of variance (ANOVA) with Tukey's honestly significant difference (HSD) test (p < 0.05).ResultsGroup B (nano) exhibited the highest fluoride (8.4 ± 0.2 ppm at 3 h) and calcium ion release (1.3 ± 0.08 ppm at 3 h), and the most alkaline pH (6.6 ± 0.09 at day 28). Particle size reduction significantly increased ion release and pH over time but reduced compressive strength (99.02 ± 4.01 MPa) and prolonged setting time (426 ± 10.14 s). The hybrid group (Group C) demonstrated a balanced profile between ion release and mechanical strength, with no chemical alteration observed across groups.ConclusionReducing GIC particle size to the nanoscale enhances ion release and alkalinity but compromises mechanical strength. A hybrid formulation incorporating both nano- and submicron-sized particles provides an optimal balance between bioactivity and strength, offering a promising direction for future development of GICs.